2021
DOI: 10.3390/ani11102939
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Wool Characteristics across the Body in a Herd of Alpacas Kept in Poland

Abstract: Wool characteristics vary depending on where on the body the wool is produced. Knowledge of this variation is important in order to separate the fleece into more homogenous parts. Similar parts from different animals can then be pooled to create batches of wool with similar characteristics. This will allow for better alpaca products with less variation. The aim of this study was to determine the variation in fiber diameter, medullation, and staple length across the body of alpacas from one herd. Wool samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The sex has no effect on MFD, in agreement with Lupton et al (2006) and Quispe et al (2021b). In Ecuador, Simbaina and Raggi (2019) and Simbaina-Solano et al (2016) found no statistical differences between sexes, but in Polish alpacas, Radzik-Rant et al (2021) reported greater MFD in males (27.15 μm) than in females (23.46 μm).…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…The sex has no effect on MFD, in agreement with Lupton et al (2006) and Quispe et al (2021b). In Ecuador, Simbaina and Raggi (2019) and Simbaina-Solano et al (2016) found no statistical differences between sexes, but in Polish alpacas, Radzik-Rant et al (2021) reported greater MFD in males (27.15 μm) than in females (23.46 μm).…”
Section: Figuresupporting
confidence: 68%
“…According to the Peruvian Technical Standard, a staple length of 65 mm is adequate for the combing system in the extra-fine category and 70 mm for other alpaca categories (NTP, 2019). In white, light-fawn, and light-brown Polish Huacaya alpacas (3-5 years old) the staple length is high at 12.8 ± 3.5 cm, where shearing is not annual (Radzik-Rant et al, 2021). Machaca et al (2017) reported differences in fiber length by location between herds from neighboring communities in alpacas from the Apurimac region, Peru.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation